2022
DOI: 10.17221/58/2021-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rootstocks on the growth, yield and fruit quality of hybrid grape varieties in cold climate condition

Abstract: Viniculture in colder countries requires the use of rootstocks adapted to the climatic and soil conditions, which influence the essential characteristics of the vine yield in terms of the physiological and morphological features. The current study was carried out in 2015–2018 in southern Poland to examine the impact of the ‘5BB’, ‘125AA’, ‘101-14M’, ‘SO4’ and ‘Börner’ rootstocks on the growth, yield and fruit quality of three grape varieties: ‘Seyval Blanc’, ‘Johanniter’ and ‘Solaris’. The following biometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
3
2
0
Order By: Relevance
“…Rootstock selection affected several growth parameters, such as total shoot length, pruning weights, trunk diameter, and trunk circumference. These results align with other studies that have shown the effect of rootstocks on shoot growth [18][19][20] and trunk size [9,19,21]. Shoot length at véraison (historically for this site) was the longest in Sauvignon blanc grafted onto 101-14MGT.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Rootstock selection affected several growth parameters, such as total shoot length, pruning weights, trunk diameter, and trunk circumference. These results align with other studies that have shown the effect of rootstocks on shoot growth [18][19][20] and trunk size [9,19,21]. Shoot length at véraison (historically for this site) was the longest in Sauvignon blanc grafted onto 101-14MGT.…”
Section: Discussionsupporting
confidence: 90%
“…Multiple growth factors such as phenology, senescence, total shoot length, trunk size, and carbohydrate reserves all showed significant variation as a function of rootstock. Although there are not many studies on the effect of rootstock on vineyard establishment, these results support other findings that show rootstocks can influence various growth factors [9,[18][19][20][21][22]. In this study, rootstock selection had an effect on phenology and senescence.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations